2019
DOI: 10.1186/s12974-019-1634-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of Toll-like receptor 4 in apoptosis of brain tissue after induction of intracerebral hemorrhage

Abstract: BackgroundInflammation and apoptosis caused by intracerebral hemorrhage (ICH) are two important factors that affect patient prognosis and survival. Toll-like receptor 4 (TLR4) triggers activation of the inflammatory pathway, causing synthesis and release of inflammatory factors. The inflammatory environment also causes neuronal apoptosis. However, no studies have reported the role of TLR4 in inflammation and apoptosis.MethodsWe performed survival curve analysis and behavioral scores on TLR4 knockout mice and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…It has been confirmed that the TLR pathway is involved in the inflammation response and diseases of CNS. TLR4 knockout inhibits the expression of inflammatory factors IL-1 β and TNF- α and improves the survival rate after induction of intracerebral hemorrhage (ICH) compared with wild-type (WT) mice [ 108 ]. TLR4 deficiency suppresses the inflammatory factors IL-1 β and TNF- α and improves cognitive dysfunction in β 2-microglobulin- (B2M-) induced age-related cognitive decline compared with WT mice [ 109 ].…”
Section: Sirt1 and Neuroinflammationmentioning
confidence: 99%
“…It has been confirmed that the TLR pathway is involved in the inflammation response and diseases of CNS. TLR4 knockout inhibits the expression of inflammatory factors IL-1 β and TNF- α and improves the survival rate after induction of intracerebral hemorrhage (ICH) compared with wild-type (WT) mice [ 108 ]. TLR4 deficiency suppresses the inflammatory factors IL-1 β and TNF- α and improves cognitive dysfunction in β 2-microglobulin- (B2M-) induced age-related cognitive decline compared with WT mice [ 109 ].…”
Section: Sirt1 and Neuroinflammationmentioning
confidence: 99%
“…Caspase3/7 activity doubled in the site ipsilateral to the transient 30 min occlusion but was 3 × in the site ipsilateral to the permanent occlusion, accurately mirroring the infarct volume data. Increased cytochrome c, a pre-cursor to caspase-3 cleavage in the intrinsic apoptosis pathway has been reported at 24 h in rat ICH models involving autologous blood-injection 31 and increased apoptotic activity has been reported at the same time point in rat 32 and mouse models 33 of collagenase injections. Caspase activity was increased fourfold in the ipsilateral cortex in our model, which was ~ 2 × that seen in the MCAo and DCAL models at the same timepoint.…”
Section: Discussionmentioning
confidence: 94%
“…ICH occurs when blood vessels in the brain rupture due to various pathological conditions, such as hypertension and microangiopathy [ 192 ]. Blood leakage in the surrounding tissue leads to edema, changes in cerebral blow flow (CBF), and neuronal injury with various mechanisms, including activation of inflammatory cascades [ 193 , 194 ]. Both the primary ICH and the surrounded cerebral edema play a critical role in post-hemorrhagic secondary brain injury [ 195 , 196 ].…”
Section: The Role Of Toll-like Receptors In Cvdsmentioning
confidence: 99%